Clothing quality evaluation and decision making in online shopping between selected fashion-conscious and less fashion-conscious consumers - Gonzales, Adrienne Marie P. (College of Home Economics, University of the Philippines Diliman, 2023)
The lack of sensorial experience has been one of the catalysts of inaccurate evaluation of clothing items during online shopping. Product information, such as sizing and fabric quality which are significant considerations in a consumer’s decision making process, impede the purchase decision. In these situations, consumers become more vigilant to avoid substandard products. However, clothing quality evaluation practices that lessen doubt and suspicion are still unclear. Therefore, this study aimed to identify the quality criteria used by the fashion-conscious and the less fashion-conscious working males and females at the pre-purchase stage of the decision making process. This study used a mixed-method approach, specifically a descriptive-qualitative approach. The Fashion Interest and Preferences Scale (FIPS) was used to measure the fashion consciousness of the respondents to classify them into fashion-conscious and less fashion-conscious consumers (n=107). A subsample of 20 respondents was asked to participate in a semi-structured interview to elaborate on their answers from the FIPS. The data gathered were analyzed using descriptive statistics and content analysis. Results show that fashion-conscious and less fashion-conscious consumers use basically the same shopping practices, quality criteria, and decision making processes when online shopping. These consumers primarily buy new clothes when the occasion arises. Online reviews, personal experiences, and friends’ recommendations are sources of reliable information about clothing quality and seller trustworthiness. Furthermore, the respondents use quality cues such as material, price, sizing, and style to make decisions. Finally, consumers use decision rules such as lexicographic, affect referral, and compensatory in selecting the most satisfactory and most value-for-money clothing item. Major recommendations from this study include evaluation tips for online shoppers, the specific information and guidelines that sellers should provide to enhance trustworthiness in online shopping platforms, and additional content for Consumer Education courses, including the principles of online selling, marketing, and shopping etiquette. Future study includes improving the psychometric property of the instrument, the FIPS.